CHROMOSOMAL DEFECTS IN INCREASED NUCHAL TRANSLUCENCY FETUS (Vietnam Journal of Community Medicine, 2021)
Objectives: Determination of the prevalence of all chromosomal defects and its distribution in fetuses with increased nuchal translucency thickness. Methodology: This is a retrospective study among pregnant women indicated for amniocentesis by nuchal translucency above 2.5 mm and consent to the study. 2720 cases were included to the study during 6 years’ period from 2015 to 2020. All singleton pregnancies whose nuchal transluciency measurements were equal or over 2.5mm, were indicated for amniocentesis. Results: The study was consist of 2720 amniocentesis in which fetal nuchal transluciency was elevated. The median maternal age was 29.19 years old (range 17-46), and the median fetal crown-rump length was 66.9 mm (range 45– 84). The fetal karyotype was abnormal in 560 (20.6%) pregnancies. The popular chromosomal conditions were including trisomy 21(55%), trisomy 18 (11.2%), trisomy 13 (3.9%), 45, XO (2.7%). Chromosomal aberrations rate was 17.6% at maternal age of 30- 34, 34% and 50.0% at maternal age of 35- 39 and ≥ 40 respectively. Conclusion: In fetuses with increased nuchal translucency, more than a half of the chromosomal aberrations were trisomy 21 (55.0%). Structural rearrangements were 22.5%. Advanced maternal age (above 35) increases the risk of chromosomal aberrations.
Keywords: Amniotic fluid, Chromosomes, Amniocentesis, Abnormal fetal chromosome